A comparism of child's right to education under islamic law and the convention on the rights of the child - Alhaji, Umar Alkali; Mohd, Azizah; Abubakar, Muhammad Alhaji (Innovative Journal, 2015)
Education is the best gift a society can give to its young ones. The importance of knowledge as the back born for development needs not be over emphasized. Where a society is educational backward, such a society is undoubtedly left behind and its future development in all spheres is threatened. Since children are the leaders of tomorrow, impacting education on children will therefore be a very important tool for measuring whether such a society is likely to prosper. This is because where children are not trained and given the necessary education; they will turn against the society and become a problem for the people. It is therefore in the interest of the society to ensure that its future leaders are trained and given all the support and encouragement so that they will be part of the train of success and prosperity for their society. In appreciation of this fact, Islamic law and the CRC guaranteed every child the right to education and stated that every child must be given the required education for him to reach adulthood as a responsible person that will be part and parcel of the development of his society. The paper therefore intends to examine the position of child’s right to education under Islamic law and the CRC in view of the fact that education is viewed as the greatest asset parents or the society can give to its future leaders.